Family perception of the process of organ donation. Qualitative psychosocial analysis of the subjective interpretation of donor and nondonor families - López Martínez, Jorge S.; Martín López, María Jesús; Scandroglio, Barbara; Martínez García, José Manuel (The Spanish Journal of Psychology, 2008)
Family perception of organ donation has been explored by numerous authors using statements by the people who decided whether or not to donate the organs of a relative in a situation of brain death. Within this tradition, in this work, we analyze the discourse of six families who granted permission for organ donation and three who refused. We describe the process-based interpretation of this experience and identify psychosocial variables and processes that further our understanding of the decision finally adopted. We have identified two heuristics that guide family decision when organ donation is requested: the explicit or inferred will of the deceased and family attitudes to organ donation and transplant. It is postulated that the interaction of these two factors explains a large amount of the decisions made. We also hypothesize that a marked discrepancy between these two factors increases the importance of other aspects, especially the role of the transplant coordinator and of other healthcare personnel. These results support, at a social level, the implementation of transplant promotion programs; and at a healthcare level, the combined use of techniques of crisis intervention and attitude change.